POLKA Interactive Media Assisted by Dolanan Songs to Increase the Creativity of Class IV Students - Carolin, Ashley Rahma; Deasylina da Ary (Universitas Pendidikan Ganesha, 2025)
Learning dance in elementary schools still faces obstacles in delivering engaging and interactive materials. This study aims to develop and test the feasibility and effectiveness of interactive POLKA (Pattern Floor Creation) media assisted by dolanan songs in increasing students' creativity in floor pattern material. The method used is Research and Development with the ADDIE approach. The subjects of the study involved expert validators of material and media, homeroom teachers of grade IV, and 20 students. Data were collected through performance tests, observations, interviews, questionnaires, and documentation. Data analysis techniques include qualitative, quantitative, and inferential statistical descriptions. The development of this POLKA media combines several elements that can be accessed simultaneously, this feature is designed to create an interactive learning experience. Based on the results of the study, the interactive POLKA media was declared suitable for use in dance learning for grade IV elementary school, interactive POLKA media assisted by dolanan songs is an effective and innovative tool to increase the creativity of grade IV students in learning in elementary schools. The use of POLKA media can be an innovative solution to increase student involvement in dance learning and encourage increased student creativity. The implications of this study indicate that the use of interactive POLKA media assisted by dolanan songs can be an alternative innovative learning strategy to improve student creativity in elementary schools, especially grade IV.